2013
DOI: 10.4236/ijcm.2013.49068
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Baroreflex Function on Blood Pressure Variability

Abstract: Objective: The aim of this study was to assess the relationship of blood pressure variability (BPV) and heart rate variability (HRV) to investigate the effect of baroreflex function on blood pressure variability. Methods: This study consisted of 111 subjects, including 32 normotensives and 79 hypertensives. All the subjects were given two concurrent tests: 24-hour Holter ECG and ambulatory blood pressure monitoring. According to standard deviation of normal-to-normal sinus RR intervals (SDNN) derived from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…In addition, this study demonstrated a reduction in the baroreflex control of heart rate in prehypertensive individuals when compared to normotensive individuals, a factor that may also be related to the increased pressure variability and peripheral sympathetic modulation observed. 34 The results of this study corroborate the findings of previous studies 9 , 11 , 13 that also observed reduction of baroreflex sensitivity in prehypertensive patients. However, this is the first to demonstrate autonomic changes in prehypertensive patients with FHSAH in relation to normotensive individuals with the same risk factor.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, this study demonstrated a reduction in the baroreflex control of heart rate in prehypertensive individuals when compared to normotensive individuals, a factor that may also be related to the increased pressure variability and peripheral sympathetic modulation observed. 34 The results of this study corroborate the findings of previous studies 9 , 11 , 13 that also observed reduction of baroreflex sensitivity in prehypertensive patients. However, this is the first to demonstrate autonomic changes in prehypertensive patients with FHSAH in relation to normotensive individuals with the same risk factor.…”
Section: Discussionsupporting
confidence: 92%
“…Both of them found that baroreflex function had effects on BPV. Aging and hypertension could increase the arterial stiffness and damage the baroreflex sensitivity, which in turn had influence on BPV [29]. In the Fluckiger's study, they also indicated that the baroreflex gain was negatively associated with age [30].…”
Section: Discussionmentioning
confidence: 95%
“…However, there was no clear physiological mechanism to explain this phenomenon. We speculated the reasons according to Imai [28] and Wei's research works [29] about the BPV. Both of them found that baroreflex function had effects on BPV.…”
Section: Discussionmentioning
confidence: 98%
“…However, the BP level in patients with hypertension as a confounding factor may affect the relationship between BPV and cardiovascular disease. Previous study had showed that hypertension could increase the arterial stiffness and damage the baroreflex sensitivity, which in turn influenced BPV [21]. Therefore, we analyzed the relationship between BPV and arterial stiffness in participants with prehypertension.…”
Section: Discussionmentioning
confidence: 99%